Transferência de aprendizagem, impacto do treinamento no trabalho, suporte à transferência de treinamento e produção acadêmica: estudo em uma universidade pública brasileira - Costa, Tatiana Pereira Athayde (2013)
This study aimed to identify the impact transfer of learning, impact of training at work and transference support of training on job performance of graduates of doctoral programs that act as teachers in a Brazilian public university. However, as it was not achieved the minimum number of participants required to test this model, there were only statistical analyzes corresponding to the other objectives of this study. The sample consisted of 74 teachers, whose titer was obtained between the years 2006 and 2009. Most acts exclusively on undergraduate (68%), while others work in undergraduate and graduate programs (32%). Data were obtained through three psychometric scales. All instruments showed satisfactory psychometric. Work performance was measured as the academic logged in Lattes (amount of articles, full papers, chapters and books), considering the three years following the year of defense from the doctoral course of each teacher. The results indicated that for teachers who work in this university, graduate school resulted in learning specific and general skills. They seem to possess a high degree of mastery in relation to skills, although they have signaled they do not use so often. In general, contrary to what the literature indicates, for this sample the correlations between variables support the transfer of training and performance at work were not significant. Participants also responded to two open questions, whose answers were analyzed by content analysis of Bardin (2011). This analysis revealed the importance of other types of support received by teachers, such as financial aid, support for entry into graduate and human resources support. The records about the types of support received not related to, primarily, the location and resources for research, financial aid and time to devote to research activities. We attempted to identify whether there were significant differences between groups of teachers divided by area of knowledge (humanities, hard sciences and biomedical) and by level of activity (work exclusively on undergraduate or simultaneous activities at undergraduate and postgraduate). The results, contributions and limitations of the study are discussed.